(untitled) (Research, Society and Development, 2024)
Non-surgical endodontic retreatment is a procedure consideredas the best alternative when there is failure in previoustreatment, it consists of the execution of a new chemicalpreparation, reinstrumentation and refilling of the canals withthe aim of overcoming the failure of previous therapy It isconsidered a more conservative procedure when compared tosurgical endodontic retreatment and tooth extraction. Furthermore, possible cases of failure in endodontic treatmentsare the result of microbial or non-microbial factors. However, in order to obtain a good treatment result, it is necessary a correct select of the case and carry out all operative steps, evena efficient coronary shielding. The purpose of the present studyis to report a clinical case of non-surgical endodonticretreatment in upper incisors that failed the initial endodontictherapy. The patient complained of pain on palpation in dental units 12 and 22 that had already been endodontically treated, and non-surgical endodontic retreatment was proposed toresolve the clinical condition. The approach adopted was theremoval of root canals, completion of all operative stages ofendodontic treatment and definitive restoration of both teeth. It is noteworthy that when correctly indicated, endodonticretreatment is the first therapeutic option with high rates ofclinical, radiographic and tomographic success, guaranteeingpatient satisfaction.